2022
DOI: 10.5603/fm.a2021.0076
|View full text |Cite
|
Sign up to set email alerts
|

A potential role of mesenchymal stem cells derived from human umbilical cord blood in ameliorating psoriasis-like skin lesion in the rats

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited. Articles in "Folia Morphologica" are listed in PubMed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…Electron microscopy showed that the epidermis of psoriasis cured by hUC-MSCs had uniform thickness, complete epidermis layers, clear boundary between the dermis and the epidermis, complete basement membrane, and no gap between tightly connected basal layer cells and basement membrane. Moreover, hUC-MSCs treatment could also reduce the expression of CD4, CD8 and CD31 in T cells ( 18 ). hUC-MSCs can significantly reduce the severity and development of psoriasis, inhibit the infiltration of immune cells into the skin, and downregulate the expression of various proinflammatory cytokines and chemokines, including first inhibiting neutrophil function and then downregulating the production of type I interferon in plasmacytoid dendritic cells ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Electron microscopy showed that the epidermis of psoriasis cured by hUC-MSCs had uniform thickness, complete epidermis layers, clear boundary between the dermis and the epidermis, complete basement membrane, and no gap between tightly connected basal layer cells and basement membrane. Moreover, hUC-MSCs treatment could also reduce the expression of CD4, CD8 and CD31 in T cells ( 18 ). hUC-MSCs can significantly reduce the severity and development of psoriasis, inhibit the infiltration of immune cells into the skin, and downregulate the expression of various proinflammatory cytokines and chemokines, including first inhibiting neutrophil function and then downregulating the production of type I interferon in plasmacytoid dendritic cells ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study testing a treatment with umbilical cord-derived MSCs (UC-MSCs) resulted in comparison with the conventional treatments (betamethasone cream) on imiquimod-induced psoriasis-like skin lesion in adult male albino rat model. MSCs showed efficacy in reducing the severity of the disease, demonstrating that the cells had anti-inflammatory and immunomodulatory effects by inhibiting the clinical manifestation [55].…”
Section: Application Of Mscs In Autoimmune Skin Diseasesmentioning
confidence: 99%
“…Therefore, keratinocytes can trigger psoriasis and actively participate in a complex environment coordinated by cytokines [54]. The treatments depend on the severity of the disease, from topical agents and phototherapy to the usual immunosuppressant drugs [55]. However, these therapies are expensive and are related to adverse reactions, and therefore, there is a need to discover a more effective and safer treatment.…”
Section: Application Of Mscs In Autoimmune Skin Diseasesmentioning
confidence: 99%
“…With advancing technology for administering MSCs, the application of MSCs has emerged as a promising strategy for the treatment of skin inflammatory disease due to their capability of regeneration, immunomodulation, and differentiation ( 45 ). Recent research found that MSCs have efficacy in the reduction of disease severity and epidermal thickness, arranging layers of epidermal layers, and keeping an intact basement membrane through its powerful capability of immunoregulation ( 46 , 47 ). MSCs can be harvested from different tissues as mentioned before, whereas from different resources MSCs may have various therapeutic effects on skin inflammatory diseases.…”
Section: The Effects Of Mscs From Different Resources On Ad and Psori...mentioning
confidence: 99%